Induction of pan-azole resistance in Cryptococcus neoformans by agrochemical azole uniconazole through upregulation of efflux and chromosomal disomies - Zhang, Maoji; Ma, Weihua; Wang, Jing; Yang, Feng; Zhong, Jingjing; Xu, Yi (Frontiers in Cellular and Infection Microbiology, 2025)
Cryptococcus neoformans is a fungus naturally found in the environment, particularly in soil, bird droppings, and trees. Cryptococcosis, caused by Cryptococcus spp., primarily C. neoformans and C. gattii, poses a significant threat to human health. Agrochemicals are widely used worldwide, and most applied agrochemicals are dispersed into the environment, which can have direct and indirect effects on human health. This study investigates the impact of the plant growth regulator uniconazole (UCZ) on antifungal resistance in C. neoformans using the H99 laboratory strain. We found UCZ to have potent antifungal activity, and exposure to UCZ induced genomic alterations, resulting in cross-resistance to both agricultural and medical azoles. The adaptors showed altered gene expressions across the genome, including efflux genes, as well as increased efflux pump activity. Deletion and overexpression of AFR1 demonstrated its role in mediating resistance to azoles, with unexpected effects on amphotericin B sensitivity. These findings underscore the significant impact of agricultural agrochemicals on antifungal resistance development and the importance of considering environmental exposures in resistance management strategies.